Structural analysis of cellulose acetate and zirconium alkoxide hybrid fibres. Issue 51 (10th May 2016) - Asai, Hanako; Nitani, Hiroaki; Nishimura, Fumihiro; Yonezawa, Susumu; Nakane, Koji
Abstract : We investigated the detailed structures of organic–inorganic hybrid fibres composed of cellulose acetate (CA) and zirconium alkoxides (Zr(OR)4 ) using various measurements. Abstract : We investigated the detailed structures of organic–inorganic hybrid fibres composed of cellulose acetate (CA) and zirconium alkoxides (Zr(OR)4 ) using attenuated total refraction-Fourier transform infrared spectroscopy (ATR-FTIR), energy-dispersive X-ray spectroscopy (EDS), and X-ray absorption fine structure (XAFS) measurements. The fibres were prepared by an air-gap spinning technique, where the acetone solution of CA was injected into a Zr(OR)4 –acetone bath. The Zr contents in the prepared fibres increased with increasing Zr(OR)4 bath concentration, but reached steady-state values at Zr(OR)4 bath concentrations above 10 wt%. In addition, EDS analysis for the cross-section of the fibre showed that Zr distribution in the fibre varied depending on Zr(OR)4 bath concentration and alkoxide type. ATR-FTIR and XAFS analysis showed that Zr contained in a CA fibre was hexacoordinated, with a local structure similar to that of hydrolysed Zr(OR)4 . This result indicated that the confinement to the CA fibre had little influence on the local structure of Zr.